1991
DOI: 10.1016/s0006-3495(91)82061-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Fourier analysis of video photobleaching measurements. Principles and optimization

Abstract: The major use of the fluorescence recovery after photobleaching (FRAP) technique is to measure the translational motion of the molecular components in various condensed media. In a conventional laser spot photobleaching experiment, a photomultiplier is used to measure the total brightness levels of the bleached region in the sample, so no spatial information can be directly obtained. In video-FRAP, a series of images after photobleaching is acquired, allowing the spatial character of the recovery to be determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 21 publications
0
103
0
Order By: Relevance
“…Long-range diffusion coefficients parallel and perpendicular to the barriers were calculated from images capturing the recovery process using a 2-dimensional Fourier transform method 20,21 . Briefly, if C(x,y,t) represents the 2-dimensional concentration profile of a diffusing species (i.e., an image of a fluorescent marker) at some time, t, and Ĉ (u, v, t) is the Fourier transform of this data, then u,v,0) represents the transform of data collected at time t=0, and D x and D y are long-range diffusion coefficients along two primary, independent axes.…”
Section: Anisotropic Diffusion Of Nanopatterned Lipid Bilayersmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-range diffusion coefficients parallel and perpendicular to the barriers were calculated from images capturing the recovery process using a 2-dimensional Fourier transform method 20,21 . Briefly, if C(x,y,t) represents the 2-dimensional concentration profile of a diffusing species (i.e., an image of a fluorescent marker) at some time, t, and Ĉ (u, v, t) is the Fourier transform of this data, then u,v,0) represents the transform of data collected at time t=0, and D x and D y are long-range diffusion coefficients along two primary, independent axes.…”
Section: Anisotropic Diffusion Of Nanopatterned Lipid Bilayersmentioning
confidence: 99%
“…The initially round photobleach spot becomes elongated, illustrating the anisotropic properties of this surface and faster long-range diffusion in the vertical direction. At later timepoints, no evidence of the initial photobleach pattern remained, indicating that there is essentially no immobile fraction of TR-DHPE lipids.Long-range diffusion coefficients parallel and perpendicular to the barriers were calculated from images capturing the recovery process using a 2-dimensional Fourier transform method 20,21 . Briefly, if C(x,y,t) represents the 2-dimensional concentration profile of a diffusing species (i.e., an image of a fluorescent marker) at some time, t, and Ĉ (u, v, t) is the Fourier transform of this data, then u,v,0) represents the transform of data collected at time t=0, and D x and D y are long-range diffusion coefficients along two primary, independent axes.…”
mentioning
confidence: 99%
“…The average intensity measured immediately after a subsequent, extended photobleach period was used to determine background intensity and subtracted from values used for this calculation. The diffusion coefficient for hEFG was calculated by following the time evolution of a nonuniform distribution of Cy5-labeled hEFG by electrophoresis, 29 as detailed in the Results and Discussion.…”
Section: Substrate Preparationmentioning
confidence: 99%
“…Diffusivities were calculated by fitting the fractional recovery of the bleached area against frequency-scaled time, where fractional recovery was measured by the decay of the spatial Fourier transforms of the images. 23,24 Bound fraction was taken as proportional to the amount of fluorescence that did not recover. Stable background fluorescence intensity measurements confirmed that this permanent bleaching was not due to bleaching of the sample from imaging.…”
Section: Image Processing and Calculation Of The Diffusion Coefficientmentioning
confidence: 99%